Evaluation Market Investment Resources in Construction Industry (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The market of investment resources in construction industry is a complicated open system of relations between different subjects of investment process and has special characteristics as well as some features common for all the markets. Development of the investment resources market influences the efficiency of the national economy, characterizes formation of basic production resources (basic, circulating and human capital) and possibilities of restructuring of the majority of industries of the country’s economy that  can encourage solving of social and economic problems.The developed market of the investment resources in construction industry is a necessary form of solving existing contradictions between needs of the branch in additional investment resources and its limited supply. As a complex of different mechanisms, it fosters not only accumulation of necessary resources but also their rational placement.When investigating the functions of the investment resources market in construction industry it was established that it has a regulative, price-determining, intermediary and stimulatory action and their appropriate use leads to the fully functioning of the market.When processing the sequence of market analysis it was determined that this process consists of four stages. Within them investment strategy is developed and effective investment portfolio is formed. The most difficult stage of the research of the investment resources market in construction industry that requires a lot of information is forecasting of macroeconomic indicators.The system of indicators that characterize demand and supply in the investment resources market in construction industry was developed. It can be used in modelling based on econometric approachAlgorithm of demand and supply modelling in the investment resources market in construction industry than enables to make mathematical formalization of the researched category functions. The results of the modelling can become analysis tools for formation and development of the national market of investment resources in construction for all economic entities that are both producers and consumers of investment resources and services and will be able to make operational adjustments of the strategies, increase the country’s economic growth while satisfying society’s needs and profit maximization.
Keywords: market, investment resources, construction, indicators, market functions, demand, supply, modeling